An overview of physics teacher professional development activities organized within the Italian PLS-Physics plan over the past five years. Issue 1 (1st June 2022) - Michelini, Marisa; Malgieri, Massimiliano; Corradini, Olindo; De Angelis, Ilaria; Bernarduzzi, Lidia Falomo; Giliberti, Marco; Pagliara, Stefania; Pavesi, Maura; Sabbarese, Carlo; Salamida, Francesco; Straulino, Samuele; Immè, Josette
Abstract: The Italian PLS-"Piano Lauree Scientifiche" project has among its objectives the improvement of school-university cooperation, with a special emphasis on in-service teacher professional development. In pursuit of such goal, growing resources and an increasing effort to strengthen the collaboration with schools have been employed in the past years. A working group within the physics section of the PLS project has developed a questionnaire to inquire about teacher formation activities organized during the past five years. After extensive revision and testing, the university network of PLS-Physics was asked to fill the questionnaire. The resulting data from 139 initiatives provides an interesting perspective on the kind of activities, organizational choices and educational priorities for teacher professional development within the PLS-physics project.